2020
DOI: 10.2196/13780
|View full text |Cite
|
Sign up to set email alerts
|

Generative Participatory Design Methodology to Develop Electronic Health Interventions: Systematic Literature Review

Abstract: Background Generative participatory design (PD) may help in developing electronic health (eHealth) interventions. PD is characterized by the involvement of all stakeholders in creative activities. This is different from the traditional user-centered design, where users are less involved. When looking at PD from a research through design perspective, it is important to summarize the reasons for choosing a certain form of generative PD to further develop its methodology. However, the scientific liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 82 publications
0
78
0
16
Order By: Relevance
“…We can only reach the target of limiting climate change to manageable degrees if all parts of society follow in the same direction; and that includes politicians, administrators, industry, citizens, and education (Szebeko and Tan, 2010 ; Pieters and Jansen, 2017 ). Getting all important actors in society to follow this direction is important, and hence research to achieve this is needed (Vandekerckhove et al, 2020 ).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…We can only reach the target of limiting climate change to manageable degrees if all parts of society follow in the same direction; and that includes politicians, administrators, industry, citizens, and education (Szebeko and Tan, 2010 ; Pieters and Jansen, 2017 ). Getting all important actors in society to follow this direction is important, and hence research to achieve this is needed (Vandekerckhove et al, 2020 ).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…However, other user characteristics might also be of relevance when involving seniors in UCD studies. For example, Vandekerckhoven et al [ 11 ] suggested that creativity and communication are relevant and important user characteristics to consider in UCD studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of user characteristics that might be relevant for defining user subgroups include level of education and socioeconomic status [ 12 , 33 ], as well as personal qualities such as the level of communication and creativity [ 11 ]. However, in order to make the method feasible, the number of subgroups considered needs to be limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of end user involvement in the design and evaluation of digital mental health interventions being widely identi ed (11,21,22), there remains a lack of clear reporting on the methods and processes undertaken (23,24). A popular methodology outlined in the literature is Participatory Design (PD), which is the involvement of end users in the co-creation and evaluation of digital health resources, as partners (25).…”
Section: Introductionmentioning
confidence: 99%